A Destination Branding of “Kampung Batik Semarang” - Widyalintang, Ari (International Journal of Research Innovation and Entrepreneurship, 2021)
Kampung Batik Semarang is one of the tourist destinations of centers of Batik Semarangan that were revived since 2006 in the City of Semarang. Nevertheless, there are still many tourists who are not familiar with Semarang Batik Village as a tourist destination in the City of Semarang. Kampung Batik Semarang does not yet have an important visual identity to identify the characters distinguishing Kampung Batik Semarang from other tourist destinations. Kampung Batik Semarang requires a visual identity as a means of developing destination branding which aims to increase the public awareness of Kampung Batik Semarang and increase the tourist visits to Kampung Batik Semarang. Therefore, Kampung Batik Semarang requires a design of the visual identity and its application on the destination branding of Kampung Batik Semarang in the form of visual identities e.g., logo and slogan, promotional media, promotional products, and wayfinding signs. The process of designing the visual identities and its application was divided into several stages, i.e., preliminary, pre-production, production, and post-production stages. This study has produced the designs of a logo, slogan, promotional media (through and below the line), promotional products, and wayfinding signs (including informational, directional, and identificational signs).